Pengaruh Recruitment dan Pengembangan Karyawan terhadap Kinerja Kerja Karyawan (Studi Kasus pada Perum Bulog Subdivre Lampung Tengah) - Pratama, Hendri; Lelawati, Nina (Universitas Muhammadiyah Metro, 2021)
Employee work performance is the result achieved by a person both in quality and quantity according to the responsibility given to him. The formulation of the problem in this study is